2022
DOI: 10.3390/v14030496
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Deltacoronavirus (PDCoV) Entry into PK-15 Cells by Caveolae-Mediated Endocytosis

Abstract: (1) Background: Porcine deltacoronavirus (PDCoV) is a newly emerged enteric virus affecting pig breeding industries worldwide, and its pathogenic mechanism remains unclear. (2) Methods: In this study, we preliminarily identified the endocytic pathway of PDCoV in PK-15 cells, using six chemical inhibitors (targeting clathrin-mediated endocytosis, caveolae-mediated endocytosis, macropinocytosis pathway and endosomal acidification), overexpression of dominant-negative (DN) mutants to treat PK-15 cells and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Cholesterol plays an essential role in PDCoV entry into cells [ 19 , 41 ]. It could therefore be expected that statins, inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase, a key enzyme in cholesterol synthesis, reduce serum or cellular cholesterol levels, possibly inhibiting replication of coronaviruses, including PDCoV.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol plays an essential role in PDCoV entry into cells [ 19 , 41 ]. It could therefore be expected that statins, inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase, a key enzyme in cholesterol synthesis, reduce serum or cellular cholesterol levels, possibly inhibiting replication of coronaviruses, including PDCoV.…”
Section: Discussionmentioning
confidence: 99%
“…Endocytosis is mostly demonstrated by the addition of inhibitors. Common clathrin inhibitors include chlorpromazine and sucrose; common caveolin inhibitors include indomethacin, nystatin, methyl-β-cyclodextrin and genistein; common macropinocytosis pathway inhibitors include amiloride, cytochalasin and colchicine; and common forms of ATP energy suppression include sodium azide, 2-deoxyglucose and low temperature [40][41][42]. In this study, HCECs were co-incubated with chlorpromazine, indomethacin, amiloride, at 4 • C and with nanomicelles, separately, proving that the cellular uptake mechanism was energy-dependent, clathrin-and caveolin-mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was assayed as described previously ( 20 ). Briefly, ST cells were seeded into 96-well plates and treated with different concentrations of inhibitors (100 μL) for 2 h at 37°C; after two washes with phosphate buffer solution (PBS), 10 µL of cell counting kit-8 (CCK-8) solution was added to 90 µL of DMEM in each well and incubated for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Porcine deltacoronavirus enters porcine IPI-2I intestinal epithelial cells via macropinocytosis and clathrin-mediated endocytosis dependent on pH and dynamin ( 19 ). Our previous work also found that PDCoV enters PK-15 cells through caveolae-mediated endocytosis (CavME) ( 20 ).…”
Section: Introductionmentioning
confidence: 91%